Enhanced ionic conductivity of sulfide solid electrolyte with high lithium content based on cryomilling - Zhenggang Jia; Xuexi Zhang; Mingfang Qian; Yingmin Jin; Yueping Xiong (Electrochemistry Communications, 2023)
Considering the high ion conductivity and good machining properties of lithium thiophosphate (LPS), it has attracted increasing attention as a solid electrolyte for all-solid-state batteries. Chemical and thermal stability can be significantly enhanced by increasing lithium content. However, in past reports, the lithium content of LPS is commonly less than 40 %. LPS with high lithium content (Li > 40 at%) shows low ion conductivity and high grain boundary resistance. In the present work, LPS with 47.2 at% lithium was prepared by cryomilling and solid-state reaction, avoiding crystallization and adhesion in the ball milling process. By improving the ball milling process, the ion conductivity (1.36 mS/cm) and ion activation energy (10.80 kJ/mol) were optimized by 106.1 % and 41.5 %, respectively. The resulting all-solid-state battery showed a high capacity retention of 104 % after 100 cycles.